2022
DOI: 10.1172/jci156305
|View full text |Cite
|
Sign up to set email alerts
|

A p300/GATA6 axis determines differentiation and Wnt dependency in pancreatic cancer models

Abstract: Wnt signaling regulates the balance between stemness and differentiation in multiple tissues and in cancer. RNF43 -mutant pancreatic cancers are dependent on Wnt production, and pharmacologic blockade of the pathway, e.g., by PORCN inhibitors, leads to tumor differentiation. However, primary resistance to these inhibitors has been observed. To elucidate potential mechanisms, we performed in vivo CRISPR screens in PORCN inhibitor–sensitive RNF43 -mutant pancreatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 85 publications
2
34
0
Order By: Relevance
“…In pancreatic cancer, loss of P300 could mediate Wnt/β-catenin independent tumor growth, thus leading to resistance to PORCN inhibition. 130 P300 inhibition also rendered bladder cancer cells resistant to doxorubicin. 131 On the contrary, P300 encoding gene EP300 was able to combine with the COL1A2 promoter to activate its expression, thus promoting apatinib resistance in GC cells.…”
Section: Histone Modifications and Drug Resistancementioning
confidence: 99%
“…In pancreatic cancer, loss of P300 could mediate Wnt/β-catenin independent tumor growth, thus leading to resistance to PORCN inhibition. 130 P300 inhibition also rendered bladder cancer cells resistant to doxorubicin. 131 On the contrary, P300 encoding gene EP300 was able to combine with the COL1A2 promoter to activate its expression, thus promoting apatinib resistance in GC cells.…”
Section: Histone Modifications and Drug Resistancementioning
confidence: 99%
“…In glioma, P300 mediates glioma stem cell adaptive response to therapeutic stress [ 74 ]. On the other hand, in pancreatic cancer, the p300/GATA6 axis determines differentiation and Wnt dependency, and loss of EP300 leads to a phenotypic transition from the classical subtype to the de-differentiated basal-like/squamous subtype of pancreatic cancer due to the attenuation of the GATA6-regulated differentiation program [ 75 ]. Similarly, Asaduzzaman et al [ 76 ] have demonstrated that the modulation of EP300 expression alters cancer stem cell markers and anchorage independence in basal-like breast cancer models.…”
Section: Several Brd Family Members Play a Fundamental Role In Cancer...mentioning
confidence: 99%
“…Our previous in vivo CRISPR screen identified several genes whose knockout caused resistance to a PORCN inhibitor 18 . Most of these genes are known negative regulators of Wnt pathway, e.g., APC and AXIN1, so that their knockout provides downstream activation of Wnt/β-catenin signaling.…”
Section: Recurrent Fbxw7 Mutations In Rnf43-mutant/rspo-fusion Cancersmentioning
confidence: 99%
“…Wnt inhibition leads to cell cycle arrest and differentiation rather than cell death in Wntaddicted cancers 14,18,26,28 . We examined if the molecular response to anti-Wnt therapies differed in the FBXW7-wildtype versus mutant tumors (Fig.…”
Section: Fbxw7 Mutation Status Predicts Resistance To Wnt Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation